2007
DOI: 10.1016/j.cardiores.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain triggers preconditioning through activation of the Na+,K+-ATPase signaling cascade in rat hearts

Abstract: Short exposure to a low concentration of ouabain protects the heart against ischemia/reperfusion injury. This effect of ouabain on the heart is most likely due to the activation of the Na+,K+-ATPase/c-Src receptor complex and subsequent stimulation of key mediators of preconditioning, namely PLC-gamma1 and PKCepsilon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
64
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 47 publications
12
64
0
Order By: Relevance
“…PKCε-TIP inhibits activation of PKCε at the intracellular concentration of 3-10 nM and has been widely used to study the role of PKCε in cardiac function (26,31,41). A previous study has shown that 5 M of PKCε-TIP inhibits PKCε translocation in the heart of adult male rats in a Langendorff preparation (28). Consistent with the previous studies (4,28), the present study showed that PKCε-TIP had no significant effects on left ventricular function at the baseline levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…PKCε-TIP inhibits activation of PKCε at the intracellular concentration of 3-10 nM and has been widely used to study the role of PKCε in cardiac function (26,31,41). A previous study has shown that 5 M of PKCε-TIP inhibits PKCε translocation in the heart of adult male rats in a Langendorff preparation (28). Consistent with the previous studies (4,28), the present study showed that PKCε-TIP had no significant effects on left ventricular function at the baseline levels.…”
Section: Discussionsupporting
confidence: 89%
“…Hearts were treated with 5 M PKCε-TIP before and during IPC. The dosage was chosen based on a previous study that showed 5 M of PKCε-TIP inhibited PKCε translocation in the heart of adult male rat in the Langendorff preparation (28). Treatment of the heart with PKCε-TIP did not significantly alter the baseline left ventricular function before ischemia (Table 1).…”
Section: Effect Of Pkc-tip On Ipcmentioning
confidence: 99%
“…The findings presented here provide strong evidence that Na-K-ATPase ␣2 differs from ␣1 in its ability to act as a signal transducer, which carries several important implications. We and others have previously shown that activation of the sig- naling pool of Na-K-ATPase ␣1 by cardiotonic steroids is capable of protecting the heart from ischemic reperfusion injury (11,37,38,41). On the other hand, chronic stimulation of the Na-K-ATPase/Src receptor complex by either endogenous or infused cardiotonic steroids increases the generation of reactive oxygen species and induces cardiac hypertrophy and fibrosis in vivo (14,20,21,33,35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to pumping Na ϩ and K ϩ across cell membranes, it also relays an extracellular ouabain signal to intracellular compartments via activation of different protein kinases (45). Pierre and coauthors (33) have provided evidence supporting the possibility that ouabain preconditioning may be cardioprotective in the therapeutic dose range. Ouabain preconditioning at concentrations without inotropic response before ischemia initiated a cardioprotective signaling pathway that induced ROS production and required mitoK ATP channel opening (32).…”
Section: Discussionmentioning
confidence: 99%